Reaksi Pasar Atas Pemilu Presiden 2014 (Studi Pada Emiten Yang Listing di Jakarta Islamic Index) - Astuti Kurniawati; Leo Herlambang (Universitas Airlangga, 2015)
The results of the presidential elections can provide a signal for investors to make decisions to invest. The purpose of this study was to determine the market reaction to the results of the presidential elections. Market reaction in this study is indicated by the presence of abnormal returns around the announcement date and the difference in trading volume activity before and after the announcement. This study is a quantitative research by using event study method with 25 issuers that listed on the Jakarta Islamic Index during the study period. The study was conducted during the 121 days consisting of 100-day estimation period and 21-day observation period. Statistical calculation in this study showed insignificant results both in the AAR and TVR. It means there is no impact from the announcement of the presidential election’s result because the investors may have been anticipating the result of the announcement.